Prevalence of primary central nervous system tumors in Iran: a retrospective study - Ali Amini Harandi; Elham Zarifi; Mohammad Reza Shahmohammadi (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundTumors are the second-most common cause of death after cardiovascular diseases. Brain tumors are really different regarding location, symptoms and signs. The aim of this study was to determine the prevalence of different primary brain tumors in Iran. MethodsThis cross-sectional study analyzed the medical records of patients with primary brain tumor referred to university hospitals between January 2016 and January 2017. By examining the hospitalization records, clinical symptoms, pathological and imaging findings, data was collected on age, sex, hand dominance, type of tumor, and the involved hemisphere. A chi-square test of independence was used to analyze the relationship between hand dominance and tumor grade. P-values less than 0.05 were considered statistically significant. ResultsIn total, 1113 patients with brain tumor with mean age of 41.89 ± 18.06 years, including 708 males (63.6%), were studied in Tehran, Iran. The most common brain tumors were glioblastoma with a frequency of 330 (29.6%) and astrocytoma 183 (16.4%). The rarest tumor types are ependymoblastoma with a frequency of 14 (1.3%). Overall, 551 (49.5%) patients had left hemisphere and 459 (41.2%) had right hemisphere involvement. There was no significant relationship between hand dominance and tumor grade (p>0.05). ConclusionBrain tumors are more common in the fourth and fifth decades of life, and glioblastoma and astrocytoma tumors are the most common brain tumors. The sex distribution of these patients in the present study shows a higher prevalence in men. There was a significant relationship between the hand dominance in patients and contralateral hemisphere involvement.